STUDENT MOTIVATION TO CHOOSE ECONOMIC EDUCATION STUDY PROGRAM AT THE FACULTY OF TEACHER TRAINING AND EDUCATION ALMUSLIM UNIVERSITY - Suqya Rahmatin; Faizin; Zulfikar (STMIK Indonesia Banda Aceh, 2026)
This study aims to identify the motivational factors that encourage students to choose the Economics Education major at the Faculty of Teacher Training and Education , University. The approach that will be used in this study is qualitative, The location in this study is the Faculty of Teacher Training and Education, Almuslim University, specifically students of the economics education study program which was carried out in August to September 2024. The population in this study was 32 people. If the population is more than 100 people can be taken between 10% -20% or 20-30%, then the sample in this study was 32 people. Based on the results of the study, it was found that the motivation of students to choose the Economics Education Department of the Faculty of Teacher Training and Education, Umuslim, first is the student's background which includes Because of the cost/economic factor, The background of students choosing to study at Almuslim University is that the costs incurred are cheap, so it does not burden students too much. Previous educational factors, The background of choosing the Economics education major is because the major when in high school most students took the Economics education major, so at Almuslim University took the Economics Education Major to develop and expand knowledge about the previous major. The distance to campus , so the distance between campus and home is also the background for students choosing to study at Almuslim University, especially in the Economics education department.